The impact of terrorism and FDI on environmental pollution: Evidence from Afghanistan, Iraq, Nigeria, Pakistan, Philippines, Syria, Somalia, Thailand and Yemen - Bildirici, Melike; Gokmenoglu, Seyit M. (ELSEVIER SCIENCE INC, 2020)
In this study, the relationships among environmental pollution, terrorism, foreign direct investments (FDI), energy consumption and economic growth is investigated for Afghanistan, Iraq, Nigeria, Pakistan, Philippines, Syria, Somalia, Thailand and Yemen covering the 1975-2017 period utilizing Panel cointegration tests, ANOVA tests, long-run estimators and panel trivariate Causality tests. ANOVA results are in favor of evidence of homogeneity between the selected countries. Long-run estimators reveal that terrorism, FDI, energy consumption and economic growth have statistically significant effects on environmental pollution. Panel trivariate Causality test determines the causal relationship between the variables. Accordingly, one-way causal nexus from terrorism to Carbon dioxide (CO2) emissions and from FDI inflows to CO2 emissions are found in the short-run. In the long-run, with strong causality results, the evidence of bi-directional causality between CO2 emissions and other variables, namely, terrorism, FDI inflow energy consumption and economic growth are detected.
Keywords: Economic Growth; Energy Consumption; Environmental Pollution; FDI; Terrorism; Trivariate Causality Test; FOREIGN DIRECT-INVESTMENT; CARBON-DIOXIDE EMISSIONS; ECONOMIC-GROWTH; CO2 EMISSIONS; ENERGY-CONSUMPTION; HAVEN HYPOTHESIS; KUZNETS CURVE; FINANCIAL DEVELOPMENT; TRADE; MILITARIZATION; Environmental Sciences & Ecology